(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the impact of Total Quality Management (as a variable of significant importance in scientific and practical circles) on customer value in a group of private hospitals in Baghdad - Al-Rusafa. These hospitals are Al-Mustansiriya Private, Al-Waziriya Private, Al-Khayal Private, Al-Nahrain Private, Beirut Private, and Al-Dawli Private. This focus is due to the increasing number of hospitals on the Al-Rusafa side compared to the Al-Karkh side, with 45 hospitals in Al-Rusafa compared to 22 in Al-Karkh. These hospitals rely on the diversity of services provided to their customers and the adoption of different methods for delivering high-quality services, aiming to address the problem of adhering to traditional methods. A questionnaire was used as the main research tool to understand the opinions of a purposive sample consisting of managers, doctors, technicians, administrators, and nurses. A total of 160 questionnaires were distributed to the research sample, and 131 were retrieved and found valid for statistical analysis using (SPSS V.28) to explore the nature of the relationship between the research variables and to test the research hypotheses concerning the impact of Total Quality Management dimensions on customer value. The descriptive-analytical approach was adopted as it is the most suitable for achieving the research objectives. To reach the results, the research employed several statistical methods appropriate to the nature of the research objectives, such as the arithmetic mean, standard deviation, coefficient of variation, and relative importance. The research concluded with several findings, most notably that the private hospitals in Baghdad - Al-Rusafa have been able to improve their customer value through Total Quality Management by focusing on continuous improvement and customer focus. Therefore, the research recommends that hospitals should emphasize these dimensions to enhance their customer value.